Locus coeruleus in memory formation and Alzheimer's disease. (27th November 2020) - James, Tony; Kula, Bartosz; Choi, Seowon; Khan, Shahzad S.; Bekar, Lane K.; Smith, Nathan A.
Abstract: Catecholamine neurons of the locus coeruleus (LC) in the dorsal pontine tegmentum innervate the entire neuroaxis, with signaling actions implicated in the regulation of attention, arousal, sleep–wake cycle, learning, memory, anxiety, pain, mood, and brain metabolism. The co‐release of norepinephrine (NE) and dopamine (DA) from LC terminals in the hippocampus plays a role in all stages of hippocampal‐memory processing. This catecholaminergic regulation modulates the encoding, consolidation, retrieval, and reversal of hippocampus‐based memory. LC neurons in awake animals have two distinct firing modes: tonic firing (explorative) and phasic firing (exploitative). These two firing modes exert different modulatory effects on post‐synaptic dendritic spines. In the hippocampus, the firing modes regulate long‐term potentiation (LTP) and long‐term depression, which differentially regulate the mRNA expression and transcription of plasticity‐related proteins (PRPs). These proteins aid in structural alterations of dendritic spines, that is, structural long‐term potentiation (sLTP), via expansion and structural long‐term depression (sLTD) via contraction of post‐synaptic dendritic spines. Given the LC's role in all phases of memory processing, the degeneration of 50% of the LC neuron population occurring in Alzheimer's disease (AD) is a clinically relevant aspect of disease pathology. The loss of catecholaminergic regulation contributes to dysfunction in memory processes along with impaired functions associated with attention and task completion. The multifaceted role of the LC in memory and general task performance and the close correlation of LC degeneration with neurodegenerative disease progression together implicate it as a target for new clinical assessment tools. Abstract : In the Alzheimer's Brian, degenerated LC input reduces hippocampal plasticity and impairs memory, whereas it promotes plasticity and memory in a health brain. Graphical artwork was done by Annabel Driussi.